Teachers’ Perception of Students’ Technology-Integrated Extramural Involvement CLIL Activities: A Cross-Country Case - Demi?Rkol Orak, Suheyla (Children Research Center, 2025)
This study examines the perspectives of CLIL (Content and Language Integrated Learning) educators in Albania, Spain, and Turkey concerning students’ involvement with technology-enhanced extramural language activities. Utilizing data from the Digital Literacies Teacher Survey (DLTS), the study examines the extent to which informal digital practices—such as gaming, social networking, streaming, and AI-enhanced tools—either augment or diverge from official CLIL instruction. The study, based on a descriptive quantitative design (N = 578), demonstrates significant variance in perceived extramural engagement, influenced by country settings, teacher training, and access to digital infrastructure. Although educators in several contexts recognized students’ significant participation in extracurricular digital language activities, their incorporation into formal pedagogy was notably restricted, especially in Turkey and Albania. Spanish educators demonstrated a heightened awareness and congruence between casual internet exposure and curriculum objectives. The results highlight the necessity for specialized teacher training and policy assistance to reconcile classroom CLIL practices with learners’ independent digital language usage, promoting context-specific models that integrate extramural involvement into bilingual and multilingual education. © 2025 Children Research Center. All rights reserved.
Öğrencilerin Teknoloji Entegreli Ders Dışı CLIL Etkinliklerine katılımına Yönelik Öğretmen Algıları: Ülkelerarası Bir Durum İncelemesi
Keywords: CLIL; Digitalization; Extramural learning; Teachers’ perceptions; Technology-integrated CLIL